Faktor-Faktor yang Mempengaruhi Struktur Modal pada Perusahaan Manufaktur Go Public di Bursa Efek Indonesia Tahun 2006-2008 (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to examine and analyze the effect of asset structure, profitability, sales growth and firm size on capital structure. The samples in this study were 54 companies in the manufacturing sector recorded in the Indonesia Stock Exchange (IDX) of the years 2006-2008, there were as many as 162 observasi. In order to test this hypothesis in this study used multiple regression. The results of this study show that: (1) The structure of assets (tangibility of assets) have a positive and significant impact on the capital structure of the company, ie, the greater the structure of assets (tangibility of assets) will increase the company's capital structure. (2) Profitability expected to have a significant negative effect on the capital structure of the company accepted, meaning that every an increase in profitability, it will be followed by a decrease in its capital structure. (3) Sales growth does not affect the capital structure of the company. (4) firm size (firm size) does not affect the capital structure of the company. Suggestions for subsequent researchers, how the impact of capital structure on the performance itself perusahaan. Therefore, other researchers who are interested in the issue of capital structure manufacturing companies can develop this research in order to determine the impact of the company's capital structure that is used to company performance.Keywords: asset structure, profitability, sales growth, firm size and capital structure.